Financial sector: Share of women on corporate boards increases slightly but men still call the shots - Elke Holst; Anja Kirsch (DIW Economic Bulletin, 2016)
In 2015, the share of women in the top decision-making bodies of the financial sector increased once again but men remain in the overwhelming majority and thus continue to call the shots. At the end of 2015, women made up just under eight percent of executive board members of the 100 largest banks in Germany. The corresponding figure for the 59 largest insurance companies was a good nine percent. In both cases, this is less than a percentage point more than in 2014. Even on supervisory boards where the share of women is traditionally higher, both banks (with just over 21 percent women on supervisory boards) and insurance companies (with just over 19 percent) have a long way to go before achieving gender parity. The proportion of women on the supervisory boards of cooperative banks was particularly low (under 16 percent) despite the fact that these institutions are, in principle, based on a participatory business model. Overall, many more women than men are employed in the financial sector. As is generally known, the presence of women in senior management in particular is a prerequisite for their promotion to top management bodies. The companies would therefore be well advised to improve the career opportunities of their most talented female employees by promoting them more frequently and appointing them to managerial positions. This would be a wise move in anticipation of a possible expansion of the statutory gender quota and a tightening of the sanctions set out in the new law on equality for women and men in managerial positions, both in the private and public sectors, which was enacted in Germany in May 2015.
Keywords: G2; J16; J78; L32; M14; M51; 330; board composition; board diversity; boards of directors; central banks; corporate boards; Europe; finance industry; financial sector; female directors; gender equality; gender quota; Germany; insurance companies; management; public and private banks; supervisory boards; women CEOs